1997
DOI: 10.1021/ac960728r
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Human Monitoring of Americium-241 Utilizing Extraction Chromatography and α-Spectrometry

Abstract: Recent developments in extraction chromatography have simplified the separation of americium from complex matrices in preparation for alpha-spectroscopy relative to traditional methods. Here we present results of procedures developed/adapted for water, air, and bioassay samples with less than 1 g of inorganic residue. Prior analytical methods required the use of a complex, multistage procedure for separation of americium from these matrices. The newer, simplified procedure requires only a single 2 mL extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Radiochemical separation is therefore required in order to avoid isobaric and polyatomic interferences (e.g. 232 U/ 232 Th) in mass spectrometry and/or spectral overlap in radiometric analyses [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Radiochemical separation is therefore required in order to avoid isobaric and polyatomic interferences (e.g. 232 U/ 232 Th) in mass spectrometry and/or spectral overlap in radiometric analyses [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Horwitz et al described a sorbent extraction methodology based on an actinide-selective extractant (0.75 M solution of octyl(phenyl)- N , N -diisobutylcarbamoylmethylphosphine oxide in tri- n -butyl phosphate) immobilized on an inert polymeric support (TRU-resin, Eichrom Industries, Inc.) . Americium separation on TRU-resin can be carried out by loading the sample in nitric acid, washing the column with additional nitric acid to remove the matrix and interferences (e.g., fission products), and eluting the Am(III) with hydrochloric acid. ,, Other tetra- and hexavalent actinides (e.g., Pu, Th, and U) will remain on the column and can be removed from the column by using ammonium hydrogen oxalate (bioxalate) as a complexing eluent. , The chemistry associated with actinide separations on TRU-resin have recently been investigated in a flow injection format …”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that leaching is not appropriate for soil containing refractory fractions. In the case of refractory residues associated with silicate lattices in the soil and air filter [ 46 ], HF in combination with other acids (typically HNO 3 and HClO 4 ) in an open vessel is a good choice for total dissolution of the matrix to release the entire Am content from the soil sample. Careful control of the physical and chemical conditions during total dissolution with an HF–HNO 3 –HClO 4 system is necessary to prevent the formation of insoluble fluorides, such as AlF 3 and CaF 2 .…”
Section: Sample Pre-treatment and Pre-concentrationmentioning
confidence: 99%